Design and test technology for dependable systems-on-chip - Ubar, Raimund, 1941-; Raik, Jaan, 1972-; Vierhaus, Heinrich Theodor, 1951- (Hershey, PA : Information Science Reference, 2011)
"This book covers aspects of system design and efficient modelling, and also introduces various fault models and fault mechanisms associated with digital circuits integrated into System on Chip (SoC), Multi-Processor System-on Chip (MPSoC) or Network on Chip (NoC)"--
Includes bibliographical references (p. 494-533) and index.
Keywords: Systems on a chip -- Design and construction; Networks on a chip -- Design and construction; Systems on a chip -- Testing; Networks on a chip -- Testing